Reducing cadmium in rice using metallothionein surface-engineered bacteria WH16-1-MT - Yu, Ying; Shi, Kaixiang; Li, Xuexue; Luo, Xiong; Wang, Mengjie; Li, Lin; Wang, Gejiao; Li, Mingshun (Environmental research, 2022)
Cadmium (Cd) accumulation in rice grains poses a health risk for humans. In this study, a bacterium, Alishewanella sp. WH16-1-MT, was engineered to express metallothionein on the cell surface. Compared with the parental WH16-1 strain, Cd2+ adsorption efficiency of WH16-1-MT in medium was increased from 1.2 to 2.6 mg/kg dry weight. The WH16-1-MT strain was then incubated with rice in moderately Cd-contaminated paddy soil. Compared with WH16-1, inoculation with WH16-1-MT increased plant height, panicle length and thousand-kernel weight, and decreased the levels of ascorbic acid and glutathione and the activity of peroxidase. Compared with WH16-1, WH16-1-MT inoculation significantly reduced the concentrations of Cd in brown rice, husks, roots and shoots by 44.0 %, 45.5 %, 36.1 % and 47.2 %, respectively. Moreover, inoculation with WH16-1-MT reduced the bioavailability of Cd in soil, with the total Cd proportion in oxidizable and residual states increased from 29 % to 32 %. Microbiome analysis demonstrated that the addition of WH16-1-MT did not significantly alter the original bacterial abundance and community structure in soil. These results indicate that WH16-1-MT can be used as a novel microbial treatment approach to reduce Cd in rice grown in moderately Cd-contaminated paddy soil. •The engineered WH16-1-MT strain increased Cd removal efficiency from medium and soil.•WH16-1-MT improved plant height, panicle length and thousand-kernel weight.•WH16-1-MT decreased the activities of antioxidant enzyme under Cd stress conditions.